Nome wharf showing the Alaska Mercantile Co. building, September 19, 1905 - Nowell, Frank H., 1864-1950 (1905)
Caption on image: Busy day on Nome wharf. Sept. 19th 1905. Nome Alaska. Photo by F.H. Nowell, 4434 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number